Four-order temperature protection for high-power 256-step LED current dimming chip. (November 2017) - Hsia, Shih-Chang; Peng, Jing-Jyun
Abstract: This study presents a high-resolution current-mode approach for LED dimming. We propose the 256-level currents to control LED brightness with 8-bit binary code. Based on current mirror theory, a switchable current is controlled by 8-switch current mirror arrays. To prolong the lifespan of LED driver, four order of the temperature sensor is proposed to control LED driving current. The diode is used as temperature sensor. In order to protect over heating of LED driver, the four sensing levels are used to control LED current. The over voltage protection is also designed to avoid to damage power MOS of this chip. With full-costumed design, the chip area included pads is only 1.87  mm 2 using TSMC 0.25  μm high-voltage technology. The single chip can drive 72 W LED devices in maximum when the LED driving current is 1.2 A and the supply voltage is 60 V. The 256-step current levels are used for LED dimming, where the resolution of current to luminance can achieve 1 mA. The maximum driving efficiency can be up to 98%, and our lighting efficiency can be improved by 20% compared with switching modulation.